TANGGAPAN MASYARAKAT MUSLIM TERHADAP SISTEM LIBERALISME DIINDONESIA - Indah Qonaah; Nola Oktavia Arista Damayanti; Wigiati Wigiati (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
Liberalism is a system that can influence the political economy throughout the world, a system formed based on history that influences it, this system is an influence that appears to criticize the system used in the political economy of the past, the influence of liberalism has developed in industrial countries, developing countries and in the country of Indonesia, but the operation of this system in several countries that influence the political economy has not succeeded in making the majority prosper, because the political economy system is affected by this system depending on the location of the authority or government that governs, on average this system will be very flexible if implemented in the country industry or developed countries, but in developing countries have been influenced by the existence of the system so that the system is not purely defeated. At present Indonesia is entering the era of globalization in all fields, in the Indonesian economy it cannot avoid outside forceswhich dominates the free market. For this reason, the community is required to participateplay a role in the creative economy. So with the system of liberalism as its decision-making, for more details in this paper will be explained.